Features Of Eclectic Approach to Teaching English Language (Eurasian Research Bulletin, 2022)
The article deals with the peculiarities of foreign language teaching and learning at linguistic universities. Several facts and statistics are illustrated in terms of the quality of the English language proficiency in Uzbekistan. Some difficulties that teachers and learners face on a daily basis are analyzed. To overcome these difficulties an eclectic approach is described.The author focuses on the issue of efficiency of the eclectic approach in foreign language teaching and learning